Antivirals versus vaccines - Osterhaus, Albert D.M.E. (Henry Stewart Talks, 2011)
Emerging infections in the past decades, Human respiratory viruses, The AIDS pandemic, HIV vaccine approaches, Antivirals use against HIV, Morbilliviruses, Metapneumovirus, hMPV, SARS-CoV, Candidate SARS vaccines, Vaccination of macaques against SARS, Henipahvirus, Smallpox, History of smallpox vaccination, Antiviral drugs against smallpox, Cidofovir, Human influenza: three appearances, Avian influenza A virus: adaptation, H1N1 virus: relevant mutations, The Mexican flu virus, Pre-pandemic H5N1 clinical trials, The importance of an adjuvant, Seasonal vaccine and pandemic A/H1N1, Flu drugs targets